Analysis Of The Implementation of School Safety Zones (Zoss) in Tomohon City - Ingrid Regina Lefrandt, Lucia; Lexie Egbert Rumayar, Audie (Journal of Social Science, 2024)
Tomohon City is city in the province of North Sulawesi, Indonesia, which is enclave from Regency Minahasa with amount sufficient school? many . Some schools located on the edge road main , where vehicles passing by with speed very dangerous height for children the school that will cross way to go or when going home from school. Children are often careless and spontaneous, so they have the potential to become victims of traffic accidents. Evaluation of the implementation of the School Safe Zone (ZoSS) needs to be carried out, so that the behavior of pedestrians and drop-off behavior can be known, whether they have behaved safely or not. Then we can draw conclusions whether the School Safe Zone has been effective in its implementation or not. SD Negeri 2 Tomohon and SD Lentera Harapan Tomohon are located on the edge of the main road so they were chosen as research locations because in front of these two schools there is a School Safe Zone (ZoSS) that needs to be evaluated. These two School Safe Zones will be evaluated based on the Decree of the Director General of Land Transportation Number 3582 / AJ.403 / DRDJ / 20018. The research was conducted for 3 days at each location, and was carried out directly including data on the completeness of School Safe Zone (ZoSS) facilities, data on pedestrian behavior and data on drop-off behavior. Speed data and volume data were taken based on references to the 2023 Indonesian Road Capacity Guidelines (PKJI) which will then be processed to obtain the level of service of the road sections studied. From this study, the data on pedestrian and usher behavior in both research locations can be stated as “not yet safe” with Zcount > Ztable. Based on the results of the service level analysis for the Jl. Sam Ratulangi section (SD Negeri 2 Tomohon), the capacity was obtained 3376 smp/hour, the peak hour volume ranged from 374 smp/hour – 788 smp/hour with a service level of service level B during peak hours. While for the Jl. Makmur section (SD Lentera Harapan Tomohon), the capacity was obtained 3440 smp/hour, the peak hour volume ranged from 705 smp/hour – 985 smp/hour with a service level C during peak hours. Therefore, it is necessary for schools to pay attention to educate students about safety in crossing the road, and for the government, especially the Tomohon city transportation agency, to socialize the intent and purpose of implementing the School Safe Zone (ZoSS) for other road users in order to create comfort and safety for road users